Midimew-connected mesh network - Rahman, M.M. Hafizur; Awal, Md. Rabiul (2014)
Midimew-Connected Mesh Network (MMN) is a MInimal DIstance MEsh with Wrap-around links (MIDIMEW) network of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher-level networks. In this poster, we present the structure and Network-on-Chip (NoC) implementation of the MMN. It is shown that the proposed MMN with innovative combination of diagonal and hierarchical structure, possesses several attractive features, including constant degree, small diameter, small average distance, moderate bisection width than that of other conventional interconnection networks and requires less amount of wires for the implementation of the physical links. For the implementation of NoC of MMN at least four layers are needed to implement all links of MMN level-3 network which is feasible with current and future VLSI technologies.